2016
DOI: 10.24003/emitter.v3i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Implementation IBR-DTN and Batman-Adv Routing Protocol in Wireless Mesh Networks

Abstract: Wireless mesh networks is a network which has high mobility and flexibility network. In Wireless mesh networks nodes are free to move and able to automatically build a network connection with other nodes. High mobility, heterogeneous condition and intermittent network connectivity cause data packets drop during wireless communication and it becomes a problem in the wireless mesh networks. This condition can happen because wireless mesh networks use connectionless networking type such as IP protocol which it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…They tested and compared four test scenarios in which the locations of the nodes were fixed and then mobile. Finally, they found that the overall performance of the TCP wireless mesh network improved, in terms of throughput, when IBR-DTN was applied [9].…”
Section: Related Workmentioning
confidence: 99%
“…They tested and compared four test scenarios in which the locations of the nodes were fixed and then mobile. Finally, they found that the overall performance of the TCP wireless mesh network improved, in terms of throughput, when IBR-DTN was applied [9].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, mesh network topology management in multi-robot network is necessary. There is a study of wireless mesh network implementation between nodes (laptops) using applications [19].…”
Section: Wireless Mesh For Multidisaster Robotmentioning
confidence: 99%
“…Functionality of the UNR-PF was evaluated through demonstration experiments on six service cases: a remote listening support service, a community formation service, a healthcare service, a shopping support service, an attracting customer service, and a touring support service and a shopping mall [19]. Figure 3 shows the overview of an UNR-PF and its parts.…”
Section: Ubiquitous Network Robot Platform (Unr-pf)mentioning
confidence: 99%
“…Dengan alat ini, petugas tidak perlu mengambil sampel air secara manual. Dan hasil dari sensor dapat langsung dikirim ke server melalui internet; 2) Wireless Mesh Network [2], dalam SEMAR kami menggunakan teknologi wireless mesh untuk memperlebar jangkauan komunikasi antara sensor dan server; 3) Portable Water Quality Monitoring System [3], kami mengembangkan sebuah alat portable dan murah untuk pemantauan kualitas air yang hasilnya dapat langsung dikirm ke server; 4) Coral Reef Monitoring System [4], sistem ini dibangun untuk melakukan monitoring terhadap kondisi karang pada perairan dangkal dengan menggunakan kamera aktif dan datanya langsung dikirim ke server; 5) Big Data Storage Architecture [5], data dari sensor dikumpulkan dan disimpan pada Hadoop server dengan dukungan HDFS, Yarn, dan MapReduce.…”
unclassified